Development of an automotive seat for ride comfort - Yusof, Mustafa; Abdul Rahman, Roslan (Universiti Teknologi Malaysia, 2004)
Seat is one of the main aspects to be considered when defining comfort in a moving vehicle. Experience shows that a seat produces different levels of comfort in different conditions. Comfort on automotive seats is dictated by a combination of static and dynamic factors. This project attempts to study the static and dynamic characteristics of a bus passenger seat for comfort through subjective and objective evaluation. Two surveys including pilot test were carried out to study the subjective evaluation responded directly by local users on seat comfort during their journey on road. For objective evaluation, two tests were conducted; SEAT (Seat Effective Amplitude Transmissibility) test and pressure distribution test. Both tests had been carried out under controlled and uncontrolled conditions. Experimental works in laboratory were considered as controllable. Uncontrolled condition refers to the road trials or field tests carried out in a moving vehicle which produced random vibration. Results have shown that, besides the postures and size of the passenger, the road conditions have effects on the pressure distribution and SEAT data. An improved seat structure with spring and damper properties was proven to be more effective in achieving seat vibration comfort. By improving the seat parameters according to those methods mentioned, the vehicle seats, such as bus seats, could be developed in term of ride comfort for local purposes.